2012
DOI: 10.1016/s1995-7645(12)60126-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Luffa acutangula extracts on gastric ulceration in NIDDM rats: Role of gastric mucosal glycoproteins and antioxidants

Abstract: Thus, LAM is proved to be a better alternative for treating gastric ulcers co-occurring with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…No autonomic or behavioral changes were detected during first 24 h. At the end of study no mortality was reported in animals even after 14 days of observation (Pimple et al, 2012). …”
Section: Toxicity Studiesmentioning
confidence: 90%
See 2 more Smart Citations
“…No autonomic or behavioral changes were detected during first 24 h. At the end of study no mortality was reported in animals even after 14 days of observation (Pimple et al, 2012). …”
Section: Toxicity Studiesmentioning
confidence: 90%
“…In a study performed by Pimple et al (2012), methanolic and aqueous extracts were safe in Swiss albino mice up to the dose of 2,000 mg/kg p.o. No autonomic or behavioral changes were detected during first 24 h. At the end of study no mortality was reported in animals even after 14 days of observation (Pimple et al, 2012).…”
Section: Toxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, edible natural ingredients also prevent the development of gastric ulcer in rats with diabetes, which is a risk factor for gastric ulcer (Masuda et al, 1976;Duggan et al, 1992). Pimple et al showed that co-administrations of methanolic extract of Luffa acutangula fruits and aspirin could significantly lowered ulcer index in diabetes rats in comparison with aspirin alone (Pimple et al, 2012). Not all edible, natural ingredients display the preventive efficacy in a dose-dependent manner.…”
Section: Efficacymentioning
confidence: 99%
“…Dietary nutritional components have capacity to modulate mucosal immunity, neuroendocrine functions, serotonergic metabolism, hypothalamic-pituitary-adrenal-axis and inflammatory cytokines [7]. Anti-inflammatory flavonoids and other polyphenols have been reported to be greatly beneficial in improving enteric and systemic milieu [8,9]. Pharmacological effects of triterpenoids have also been reported in several studies which modulate immune system.…”
Section: Introductionmentioning
confidence: 99%